The cross : meditations and images - Fass, Serena ([London] : Gilgamesh Publishing, 2013)
Texts on the cross accompany illustrations of representations in a variety of media from around the world and spanning from the earliest Christians in Pompeii to the present day.
Includes bibliographical references and index.
Keywords: Crosses -- Pictorial works; Christian art and symbolism